The Influence of MarvelAPP Educational Game Learning Media on the Learning Achievement of IPAS Students in Grade 5 Elementary School: The Effect of MarvelAPP Educational Games on Elementary IPAS Learning - Lely Melan Mega Auliya; Dya Ayu Agustiana Putri; Frita Devi Asriyanti (Primary Education Insight, 2026)
Students' IPAS learning achievement at the elementary school level remains relatively low due to the limited use of interactive and engaging learning media in classroom instruction. Conventional teaching methods often reduce students' participation and make it difficult for them to understand abstract concepts. Therefore, innovative digital learning media are needed to create more meaningful learning experiences. This study aimed to examine the effect of MarvelApp educational game learning media on the IPAS learning achievement of Grade 5 elementary school students. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 90 Grade 5 students, including 44 students in the experimental group and 46 students in the control group. The experimental group received instruction using MarvelApp educational game learning media, whereas the control group received conventional instruction. Data were collected using a 20-item IPAS learning achievement test administered as both a pretest and posttest. The instrument demonstrated excellent internal consistency (Cronbach's Alpha = 0.972) and acceptable construct validity. Data were analyzed using descriptive statistics, assumption tests, and an independent samples t-test. The findings revealed no significant difference between the two groups before the intervention, whereas a significant difference was observed after the intervention, with the experimental group achieving higher IPAS learning achievement than the control group (p < .001). These findings indicate that MarvelApp educational game learning media effectively enhances students' learning achievement by promoting active engagement and meaningful learning experiences.